Relato de eventos predatórios em Lonomia spp. (Saturniidae: Hemileucinae) - Melo Favalesso, Marília (2020)
Lonomia Walker 1855 is a genus of moths in which larvae are widely known due to the occurrence of accidental contacts and can be fatal to humans. Despite their medical importance, there are few studies with an ecological focus on this genus. In order to contribute with information about predators of Lonomia spp., this note brings two reports on predation of its larvae: one made by a male bird Trogon surrucura aurantius Vieillot 1817, and other made by a bug Alcaeorrhynchus grandis Dallas 1851.